Teams Games Tournament (TGT) Method to Improve Students' Motivation in Learning Islamic Religious Education - Ajeng Nur Cahyani; Abdul Rohman (Yayasan Letiges Konsultan Sosial, 2026)
Learning motivation plays an important role in the student learning process, and learning methods can strategically increase it. This study aims to examine the increase in students' learning motivation through the use of the Teams Games Tournament (TGT) method in the learning process of Islamic Religious Education and Ethics. The research method used is qualitative, with a case study approach, to gain an in-depth understanding of how the TGT method is implemented in the classroom. Data collection was carried out through interviews, documentation observations, and questionnaires, which were then validated using triangulation techniques to ensure the accuracy and consistency of the findings. Data analysis is carried out using a flow method developed by Miles & Huberman, which includes data reduction, data preparation, and conclusions drawn. The study's findings show that the TGT method can create a more active, dynamic, and fun learning environment and increase student participation in learning activities. Before TGT was implemented, students' learning motivation was moderate, tended to be passive, and showed low initiative. After implementing TGT, there was a significant increase in enthusiasm, the courage to give opinions, involvement in discussions, and student confidence. Playing academic games and collaborating in groups also help students better understand the material.